INTERACTION ACTIVITIES EFFICACY ON LEARNERS GRAMMAR COMPETENCE - Dehaam, Qusai Mohammed; Khalaf, Muthana Hameed (Journal of Tikrit University for Humanities, 2023)
The purpose of this study is to investigate the important of grammatical teaching approaches by making compare between two approaches; traditional and communicative approach. The study was guided by tests (pre-test and post-test). Furthermore; the objective of the study to identify the appropriate and affective approaches in teaching grammar. The main significant goal was to show which approach is appropriate to enable learners achieving linguistic competence. The sample of the study was number of students in second intermediate stage in Al Aadhmia School in Baghdad city. Based on the findings of the study the researcher has found out that, second language learners would benefit of applicant of both methods in teaching grammar and concerning with knowledge rather than the use of grammatical rules in communication.